Measuring the Spatial-Physical Indexes of RahAhan and Reazashhar Neighborhoods in Mashhad Based on New Urbanism Approach - Mohammad Ajza Shokouhi; Shirin Sabaghi Abkooh; Forough Kazaei Nejad (تحقیقات کاربردی علوم جغرافیایی)
A new urbanism theory has emerged in recent decades in response to numerous urban problems of the twentieth century, with the goal of creating vibrant, compact, diverse and desirable cities in terms of work, walking, life, and transportation options. In view of the widespread acceptance of this theory among the Iranian researchers, the aim of this study is to assess the sustainability of organic and planned neighborhoods in Mashhad based on the spatial-physical indexes of new urbanism. In this regard, two neighborhoods, RahAhan (organic neighborhood) and the second phase of Rezashahr (planned neighborhood) were selected. This research method is descriptive- analytical and the mixed model of AHP and GIS has been used to assess the stability of two neighborhoods. Accordingly, the Sustainability Measurement Model was used as a hierarchy in the form of 7 physical-space indicators (type of road, pedestrian width, land use, area of lots, access to the center of the neighborhood, number of floors and access to public transport) . Tthe research results show that in Rezashhar, 68.43% of neighborhood area has moderate to high stability and 31.57%  of the total of the neighborhood area is the lack of stability, and in RahAhan, 70.84%  of the total of the neighborhood has moderate to high stability and 29.16% of the total of the neighborhood is lack of stability. Therefore, according to the spatial indicators of the new urbanism, the neighborhood of Reza Shahr is more unsustainable than the old neighborhood of Rah Ahan. Therefore, this study shows the richness of traditional Iranian urbanization and the superiority of old neighborhoods. So, it can be said that traditional and organic urbanization is a more appropriate basis for applying the new urbanism approach and this approach can be used in the form of urban regeneration.